A new 'saccamminid' genus (Rhizaria: Foraminifera), from 4400 m water depth in the Nazare Canyon (NE Atlantic) - Silva, Ana Aranda da (2012)
We describe Bithekammina occulta, a new monothalamous agglutinated foraminiferan ('saccamminid') collected in multicore samples at 4400 m on the terrace of the lower Nazare Canyon on the Portuguese margin. The test is spherical to oval, up to similar to 400 mu m in length, with a simple circular aperture. The wall has a very smooth surface with a distinct sheen in reflected light. It is <10 mu m thick and composed of very fine agglutinated plate-like clay particles and a thin inner organic layer. The most distinctive feature of the new species is that the test is contained within an agglutinated case ('secondary test') composed mainly of larger (10-50 mu m) quartz grains. The case is equipped with a long, narrow tube that originates near the aperture of the inner test and presumably acts as a channel through which pseudopodia are deployed. Secondary agglutinated structures have been described in a number of foraminifera, but never before in a 'saccamminid'.